2022
DOI: 10.1021/acs.chemmater.2c00116
|View full text |Cite
|
Sign up to set email alerts
|

π–π Interlocking Effect for Designing Biodegradable Nanorods with Controlled Lateral Surface Curvature

Abstract: The morphology of nanoparticles is closely related to their various applications. However, precise control over geometric parameters such as the lateral surface curvature (K) of nanorods still remains an important challenge. To address this issue, we propose a π–π interlocking effect for fabricating biodegradable nanorods with tailored lateral surface curvature. This interlocking effect originates from π–π interactions, provides noncovalent conformational locks among poly-γ-benzyl-l-glutamate (PBLG) chains, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…As one of the most powerful tool to prepare soft nanomaterials with precisely controlled structure and functionality, polymer self-assembly also plays important role in the fabrication of MCPs, including polymersomes-in-polymersomes, , MVVs, onion-like polymersomes , and LCVs . For instance, Cheng et al reported the preparation and self-assembly of amphiphilic polyurethane phosphate (PUP), which self-assembled into various morphologies including LCVs by adjusting the hydrophobic chain length and initial polymer concentration in the PU tail.…”
Section: Preparation Of Mcpsmentioning
confidence: 99%
“…As one of the most powerful tool to prepare soft nanomaterials with precisely controlled structure and functionality, polymer self-assembly also plays important role in the fabrication of MCPs, including polymersomes-in-polymersomes, , MVVs, onion-like polymersomes , and LCVs . For instance, Cheng et al reported the preparation and self-assembly of amphiphilic polyurethane phosphate (PUP), which self-assembled into various morphologies including LCVs by adjusting the hydrophobic chain length and initial polymer concentration in the PU tail.…”
Section: Preparation Of Mcpsmentioning
confidence: 99%
“…Furthermore, our group introduced a series of terminal groups with different π−π stacking strengths into poly-γbenzyl-L-glutamate (PBLG) homopolymers. 29 These homopolymers could self-assemble into nanorods. The lateral surface of nanorods is regulated by the strength of π−π stacking among the terminal groups.…”
Section: Hydrogen Bondingmentioning
confidence: 99%
“…Additional forces that can contribute to polymer self-assembly are p-p stacking interactions from the aromatic group on the PPhe core-forming block. 66,70 It is possible that the strength of these aromatic interactions is affected by the changing secondary structure and/or that these interactions are governed by the degree of hetero-chirality. Nevertheless, more research is required to further elucidate the driving force for this intriguing PISA formulation that is aided by the structure of the peptide chain.…”
Section: Effect Of Chirality In Cc-pisamentioning
confidence: 99%